High temperature RF performances of epitaxial bilayer graphene field-effect transistors on SiC substrate. (30th August 2020) - He, Zezhao; Yu, Cui; Liu, Qingbin; Song, Xubo; Gao, Xuedong; Guo, Jianchao; Zhou, Chuangjie; Cai, Shujun; Feng, Zhihong
Abstract: This paper investigated the temperature effects on the RF performances of the epitaxial bilayer graphene field-effect transistors (EBG-FETs) on a SiC substrate over a temperature range of 25–200 °C under the atmospheric environment. The temperature dependence of the cutoff frequency f T and the maximum oscillation frequency f max of the EBG-FETs with an identical gate-length and different gate-widths were measured by small-signal measurement up to 40 GHz. The results show that EBG-FETs are capable of operating at high temperature up to 200 °C with workable amounts of thermally induced performance degradation. To gain further insight into the underlying physics of the device parameters affected by temperature, the small signal device parameter variations with ambient temperature are discussed. This work reveals the great potential of graphene in high temperature device applications. Graphical abstract: Small signal current gain h 21 versus frequency measured in a temperature range of 25–200 °C. And the schematic diagram of dual-gated EBG-FET structure on SiC substrate. In this work, epitaxial bilayer graphene field-effect transistors (EBG-FETs) are fabricated on SiC substrate. The RF performances of the EBG-FETs are studied over a temperature range of 25–200 °C under the atmospheric environment. The results show that EBG-FETs are capable of operating at high temperature up to 200 °C. To gain further insight into the underlying physics of the device parameters affected by temperature, the small signal device parameter variations with ambient temperature are discussed. This work reveals the great potential for graphene in high temperature device applications. Image 1